A review on co-existent Epstein-Barr virus-induced complications in inflammatory bowel disease - Wu, Shuang; He, Chuan; Tang, Tong-Yu; Li, Yu-Qin (European journal of gastroenterology & hepatology, 2019)
There have been growing reports regarding the presence of Epstein-Barr virus (EBV) in the intestine portions of patients suffering from ulcerative colitis and Crohn's disease, collectively termed as inflammatory bowel disease (IBD). Indeed, the prevalence of EBV infection increases in IBD patients due to prolonged employment of immunosuppressive drugs including azathioprine and infliximab. In turn, coinfection with EBV increases the propensity of development of lymphoproliferative disorders in the gastrointestinal tract including Hodgkin lymphoma, non-Hodgkin lymphomas, and lymphoepithelioma-like cholangiocarcinoma. Therefore, it is recommended that IBD patients on prolonged immunomodulator therapy should be monitored for the presence of primary intestinal lymphoproliferative diseases. Moreover, coinfection of EBV complicates the clinical course of IBD by increasing the severity, chronicity, inducing refractoriness and increasing relapse incidences. Therefore, it is recommended that antiviral drugs should be added in the conventional IBD therapy in the suspected cases of EBV infection. Research has also revealed that EBV-induced colitis is very similar to IBD and there are chances of misdiagnosis of IBD in the presence of EBV colitis. The proper diagnosis of EBV infection along with its timely treatment is necessary to avoid the severe complications in patients of IBD. The present review discusses the role of EBV coinfection in increasing the clinical complications of IBD patients.